Conceptions of happiness and its relationship with subjective well-being: A study through Natural Semantic Networks - Flores-Kanter, Pablo Ezequiel (2018)
The pursuit of happiness is one of the most coveted goals of human beings. There are increasingly more psychology studies seeking to find which factors are involved in happiness. There are two main approaches to this study: the hedonic and the eudaemonic paradigms. The hedonic paradigm proposes that well-being depends primarily on living a life with pleasant experiences, while the eudaemonic paradigm refers that well-being is not only achieved through pleasure, but mainly through upgrading the human potential. In the present study we worked with a sample consisting of 340 citizens of Cordoba (Argentina) to investigate which conceptions they have about happiness by the technique of Natural Semantic Networks (NSN). Two hypotheses were proposed in this regard: 1) participants will conceive happiness both in hedonic and eudaemonic terms, and 2) those participants with higher levels of happiness will have a predominantly eudaemonic conception of happiness. The first hypothesis was corroborated broadly, because the definitions obtained in the total sample and in the groups being compared contained both hedonic and eudaemonic components. Likewise, evidence favoring the second hypothesis is also provided; that is, participants with higher levels of subjective happiness have a predominantly eudaemonic conception of happiness.